2009
DOI: 10.1371/journal.pone.0005289
|View full text |Cite
|
Sign up to set email alerts
|

Pain Reactivity and Plasma β-Endorphin in Children and Adolescents with Autistic Disorder

Abstract: BackgroundReports of reduced pain sensitivity in autism have prompted opioid theories of autism and have practical care ramifications. Our objective was to examine behavioral and physiological pain responses, plasma β-endorphin levels and their relationship in a large group of individuals with autism.Methodology/Principal FindingsThe study was conducted on 73 children and adolescents with autism and 115 normal individuals matched for age, sex and pubertal stage. Behavioral pain reactivity of individuals with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
115
2
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 50 publications
11
115
2
17
Order By: Relevance
“…In rats it was shown that β-CM7 ultimately triggered ASD-like behavioral changes by dietary administration of β-CM7 linked to segmented brain activity as shown before [64]. Behavior after administration of β-CM7 changed from very active and aggressive to significantly reduced responsiveness to sound, a lack of explorative behavior and reduced or absent social interaction, consistent with ASD-like behavior [9,24,60,79,93,94,95].…”
Section: Opioid Activity Of β-Cm7 and Asd Behaviormentioning
confidence: 67%
See 2 more Smart Citations
“…In rats it was shown that β-CM7 ultimately triggered ASD-like behavioral changes by dietary administration of β-CM7 linked to segmented brain activity as shown before [64]. Behavior after administration of β-CM7 changed from very active and aggressive to significantly reduced responsiveness to sound, a lack of explorative behavior and reduced or absent social interaction, consistent with ASD-like behavior [9,24,60,79,93,94,95].…”
Section: Opioid Activity Of β-Cm7 and Asd Behaviormentioning
confidence: 67%
“…In addition to DPP4 activity, these concentrations reflect intestinal permeability. Several studies found a significantly higher level of blood plasma β-endorphin, an endogenous opioid peptide in autistic subjects when compared to controls [76,94,95] and plasma β-endorphin was positively associated with the severity of ASD symptoms [95]. Moreover, an increase of β-endorphin levels in the cerebrospinal fluid was reported [79].…”
Section: Dpp4 Enzyme Activity In People With Autism Spectrum Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that some people with autism [6] have stereotyped movements, and in About analgesia, in both male and female rats exposed to VPA prenatally, the latency of withdrawal time of their tail is increased, although in female rats it only appears on day 35 and in males, this increase is maintained up to day 180. It has been reported that people who have autism have reduced pain sensitivity, however, there is a study that suggests that people with ASD do not have decreased sensitivity to pain, what happens is that they respond differently to the variety of circumstances that trigger the pain response [67]. In spite of the discrepancies about pain in people with ASD, in this model, female and male rats had a longer period of latency in the withdrawal of the tail to a painful stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of β-endorphin and ACTH are greater in autistic subjects than normal individuals (Tordjman et al, 1997). More recent work on pain perception in autism has demonstrated that in response to venipuncture, there is a greater heart rate response and elevated plasma β-endorphin levels in autism subjects compared to age-, sex-, and pubertal stage-matched controls (Tordjman et al, 2009). The results strongly suggest that prior reports of reduced pain sensitivity in autism are related to a different mode of pain expression rather than to an insensitivity or endogenous analgesia, and do not support opioid theories of autism.…”
Section: Neurologicmentioning
confidence: 99%